Some Effects of EU Sugar Reforms on Development in Africa - Johannes Paha; Timon Sautter; Reinhard Schumacher (Intereconomics, 2021)
The sugar industry is a major provider of jobs and income for sugar-exporting countries in Africa. The lower sugar prices that were caused by the recent liberalisation of the EU sugar market may not only jeopardise economic development in those countries, but the reforms also create difficulties for sugar-importing countries in Africa that seek to develop their sugar industries. The article analyses the effects of EU sugar market reforms on three African countries – Nigeria, South Africa and Mozambique – and provides insights into the balancing of the EU sugar policy's intended effects against their adverse effects on European trade and development policy.
Keywords: 330; Zucker; Außenwirtschaftspolitik; Entwicklung; Subsahara-Afrika; EU-Staaten